Themes and Variations of viral small terminase proteins - Teschke, Carolyn (2012)
Viruses are the most populous ‘biological entities’ on Earth (Krupovic and Bamford, 2011). The most common of these are the tailed, double-stranded DNA (dsDNA) containing bacteriophages, which outnumber bacteria by 10 fold. Since they do number so many, bacteriphages greatly affect global processes (Suttle, 2007). Related to dsDNA phages are the eukaryotic dsDNA Herpesviruses, which cause a host of diseases including chicken pox, shingles, Karposi’s sarcoma and mononucleosis (Cardone et al., 2012). Thus, understanding the assembly of this class of viruses is important for both the global climate and human health.